A PEMBELAJARAN PROBLEM BASED LEARNING: PEMBELAJARAN PROBLEM BASED LEARNING DENGAN BER-PRAKARYA MENGUNAKAN MEDIA LOOSE PART PADA ANAK USIA DINI KELOMPOK B - Tuti Aisyah; Raudatul Zannah; Elvinzie A.E.L; Yeni Trisilaningsih; Nina Yuminar Priyanti (Program Studi PG-PAUD Universitas PGRI Adi Buana Surabaya, 2022)
The purpose of this study was to analyze the achievement of the artistic aspect in non-formal early childhood education, namely BiMBA AIUEO. Researchers make planning activities and classroom action research that function as instilling love for the environment in students from an early age. Achieving various aspects of achievement, one of which is the aspect of art in early childhood education. Forming children's independence in solving problems in everyday life so that life skills are created through the student center learning model and problem based learning methods. The research subjects were 10 students aged in group B. The results of classroom action research on pre-cycle activities were only 37%, the category of students who had not developed in the first cycle of 44.5% began to develop and after carrying out the second cycle there was an increase to 60.5% developing as expected.